Training Need Assessment of Vegetable Farmers in Bundi District of Rajasthan (Indian Journal of Extension Education, 2011)
Due to technological advancement in vegetable cultivation, there is a strong need to train the growers to keep them abreast about improved technologies for improving their productivity and increasing income. Thus, for organizing effective training programme, the present study was planned with objective to identify the training needs of vegetable farmers. The study was conducted in Bundi district of Rajasthan to identify the training needs of vegetable growers. A sample of 120 farmers was selected through stratified random sampling technique as respondent. The selected respondents were interviewed personally with the help of a well structured and pre-tested interview schedule. The data collected were tabulated and statistically analyzed to interpret the results. The overall training need of farmers have been measured in terms of training need quotient (TNQ). It was observed that farmers required intensive training on harvest management of vegetables. Further, training need intensity of farmers in other aspects of vegetable cultivation like field preparation, seed and sowing, manure and fertilizer management, intercultural operations, plant protection and marketing was medium.